Optimization of Solid-State Fermentation Process for Dietary Fiber in Flaxseed Meal and Analysis of Its Microstructure and Functional Properties - Chunpeng Hou; Yiyang Zhang; Jiaxun Chen; Jianguo Hu; Chenxian Yang; Fusheng Chen; Tingwei Zhu; Ying Xin; Xiaohui Geng (Foods)
Flaxseed meal (FSM) is a by-product of flaxseed product production that is wasted unreasonably at present. In this study, we used Bacillus subtilis K6, a dominant microbial strain, for solid-state fermentation (SSF) of FSM following preliminary screening to improve FSM utilization efficiency and enhance the soluble dietary fiber (SDF) content while modifying its functional properties. FSM’s microstructure was characterized before and after fermentation, and the functional properties of the dietary fiber (DF) in the FSM were assessed. Single-factor experiments combined with response surface methodology were conducted to optimize SSF parameters using SDF yield as the response variable. The optimal conditions were determined as follows: 45 h fermentation time, 40.5 °C temperature, and 1:0.65 material-to-liquid ratio. Under these conditions, the SDF yield reached 33.45 ± 0.24%, an SDF yield increase of 36.92%. Scanning electron microscopy and confocal laser scanning microscopy demonstrated FSM’s structural disruption during fermentation. Furthermore, SDF and insoluble DF showed improved water-holding, oil-holding, and swelling capacities following fermentation. These results indicate that SSF effectively enhances the SDF content in FSM and optimizes its functional properties, thereby providing a theoretical foundation for the valorization of flaxseed by-products.